Analysis of Blood Biomarkers in Patients with Chronic Obstructive Pulmonary Disease (COPD) and with Asthma-COPD Overlap (ACO). (3rd May 2020) - Gava, Giordana; Núñez, Alexa; Esquinas, Cristina; Sarasate, Mikel; Loeb, Eduardo; Pirina, Pietro; Miravitlles, Marc; Barrecheguren, Miriam
Abstract: Chronic obstructive pulmonary disease (COPD) is a heterogeneous entity with different clinical phenotypes, such as asthma-COPD overlap (ACO). The aim of this retrospective study was to compare routine blood biomarkers in patients with ACO and the remaning COPD phenotypes. Data were collected from stable COPD patients visited in during 2018, including C-reactive protein (CRP), fibrinogen, neutrophyl/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR).A total of 77 patients with COPD were included, 24 (31%) fulfilled the diagnosis of ACO. Clinically, patients with ACO presented more dyspnoea and wheezing. Regarding laboratory parameters, both groups had low levels of lymphocytes, especially the non-ACO group (24.2% vs. 29.3%; p  = 0.031), patients with ACO had significantly higher eosinophil counts (4.7% vs. 1.9%; p  < 0.001) but a lower percentage of neutrophils (56.8% vs. 64.7%; p  = 0.003), NLR and PLR (2.5 vs. 3.8; p  = 0.013 and 115 vs. 160; p  = 0.063, respectively). In conclusion, besides the expected eosinophilic inflammation in patients with ACO, both groups had low levels of lymphocytes, especially the non-ACO group. The low levels of lymphocytes, in particular in non-ACO patients, should be confirmed in larger studies.